Long-Term Survival and Late Toxicity Associated With Pelvic Intensity Modulated Radiation Therapy (IMRT) for Cervical Cancer Involving CT-Based Positive Lymph Nodes - Lei, Chengzhi; Ma, Shaokang; Huang, Manni; An, Jusheng; Liang, Bin; Dai, Jianrong; Wu, Lingying (Frontiers in Oncology, 2019)
Purpose: To evaluate the outcome and toxicity of cervical cancerpatients with positive lymph nodes treated by intensity-modulated radiation therapy (IMRT) and intracavitary brachytherapy (ICBT) with concurrent chemotherapy.Methods and Materials: We retrospectively evaluated 108 cervical cancer patients of CT based positive lymph nodes treated withIMRT and ICBTwith concurrent chemotherapy between 2009 and 2011. IMRT plans were designed to deliver50Gy to 95% PTV (cervical tumor, pelvis and parametrium) with 1.6-1.8Gy daily fractions, and 60-70Gy to 95% PGTV-LN (pelvic or para-aortic lymph nodes) with 2.0-2.2Gy daily fractions.Overall survival (OS) iscalculated using the Kaplan-Meiermethod.Acute and late toxicities were evaluated according to the Radiation Therapy OncologyGroup and European Organization for Research and Treatment ofCancer toxicity criterion.Results:In the total 108 cases, 45casesare instage IIB and 63in stage IIIB. The median follow-up was 65 (range 2–83) months.Overall, the 5-year cumulative incidences of pelvic failure alone, distant failure alone, synchronous pelvic and distant failure were 8.3%, 12.9%, and 8.3%, respectively. The 5-year OS rate was 67.6%, and the 5-year progression-free survival (PFS)rate was 53.7%. The 5-year cumulative incidence of late Grade 3 toxicity or higher gastrointestinal and genitourinary toxicitiesoccurred in 9.2% patients and acute Grade 3 hematologic toxicity or higher for leukopenia was 51.8%.Conclusions: The clinical results suggest that IMRT concurrent with chemotherapy isan effective treatment with acceptable toxicity for advanced cervical cancer with positive lymph nodes.